Supply chain finance with partial credit guarantee provided by a third-party or a supplier. (September 2019) - Lu, Qihui; Gu, Jian; Huang, Jiazhou
Highlights: This study investigates two supply chain finance models with partial credit guarantee. Third-party guarantee may not always be applicable when guarantee rate is low or market risk is high. Retailer always prefers supplier guarantee model. Supplier wants to provide guarantee when retailer is relatively poor or rich. Abstract: This study investigates two supply chain finance models with partial credit guarantee (PCG) provided by a third-party or a supplier when a retailer borrows from a bank. The study evaluates the optimal order quantities of retailers and the fairly priced interest rates of banks in the two guarantee models. Findings corroborate that the financial model with third-party guarantee may not always be applicable because the profit of the third-party guarantor company may be negative when the guarantee rate is low or the market risk is relatively high. For an effective guarantee from the third-party, the retailer's optimal decision may be limited by the nonnegative condition on the profit of the third-party guarantor. Results of a comparative analysis on the two PCG models affirm that the retailer always prefers the supplier guarantee model. If the guarantee rate in the third-party guarantee model is low, then the supplier can always benefit from the supplier guarantee model, otherwise, the supplier will provide the guarantee for relatively poor or rich retailers. Surprisingly, even if the retailer is poor and the market risk is high, the supplier has an incentive to provide a guarantee. Numerical analysis finds that the preference on the guarantee model of the retailer or the supplier is quite dependent with the market risk and guarantee rate.